Water : will there be conflicts? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Over 97% of the world's water is saline and in oceans. Of the 2.5% of water which is fresh, only 3% is directly available as part of the cycle of rainfall and evaporation, in rivers and lakes; the rest is in ice, permanent snow, and fossil...